Improving English Prospective Teachers’ Translation Quality through a Small Group Discussion - Kariadi, Mustasyfa Thabib (Jurnal Bahasa Inggris, 2017)
English prospective teachers should be able to well translate any text used as their teaching materials for both junior and senior high school students. Basically translation is an individual skill, yet it is believed that more heads may gain better results. This research is intended to improve the prospective teachers’ translation quality through a small group discussion. This descriptive qualitative research uses a purposive random sampling technique with a pretest and posttest design. The research result show that the errors are made in translating specific terms used in the passage by 31%, followed by distortion of meaning by 25%, and misspelling or grammatical errors by 22%. As those error results are less than those made in pre-test which are respectively by 55%, 36%, and 26%, it can be concluded that Small Group Discussion used by the prospective teachers in translating the National Examination Text is effective with the highest errors in translating the specified terms available in the text followed by the distortion of meaning, and misspelling/grammatical errors.